2019
DOI: 10.1007/7651_2019_236
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Full-Thickness Human Skin Equivalent on an Immunodeficient Mouse

Abstract: Human skin equivalents composed of epidermal cells and fibroblasts are important for modeling human epidermal development, testing new therapeutics, and designing novel treatment strategies for human skin diseases. Here, we describe a procedure for the generation of an in vivo fullthickness human skin equivalent on an immunodeficient mouse using a grafting chamber system. The protocol involves mixing human epidermal cells and fibroblasts in a silicone grafting chamber that is surgically inserted onto the muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…To evaluate the effect of hTERT mRNA DOTAP‐A LNP on hSCS engraftment, a partial thickness wound healing model was developed in immunocompromised mice. [ 38 ] The overall flow of the experiment is summarized in Figure a. hSCS was isolated using the RECELL Device which includes enzymatic and mechanical processing steps, resulting in a cell suspension containing >50% viable cells, mainly keratinocyte and fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the effect of hTERT mRNA DOTAP‐A LNP on hSCS engraftment, a partial thickness wound healing model was developed in immunocompromised mice. [ 38 ] The overall flow of the experiment is summarized in Figure a. hSCS was isolated using the RECELL Device which includes enzymatic and mechanical processing steps, resulting in a cell suspension containing >50% viable cells, mainly keratinocyte and fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…An in vivo humanized partial‐thickness wound model was used to study human skin cell engraftment after transfection with hTERT mRNA LNP (Figure 5), modifying previously reported models. [ 38,46,47 ] Our studies have shown that hSCS engraftment was significantly improved by pretreatment with hTERT mRNA DOTAP‐A LNP as compared to untreated hSCS or hSCS pretreated with EGFP mRNA LNP. The following markers were assessed: Lamin A, Ki67, p21, and 53BP1 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human xenograft models have been previously published, including a skin flap assay ( Qiao et al, 2008 ), human skin transplantation-like approaches for grafting dermal-epidermal equivalents onto opened wounds of recipient mice ( Escamez et al, 2004 ; Martinez-Santamaria et al, 2012 ; Yanez et al, 2015 ; Jorgensen et al, 2020 ), and chamber grafting assay ( Wang et al, 2000 ; Diette et al, 2020 ). While promising, all these assays suffer from several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…They include (1) the complexity of the procedure that requires the generation of 3D skin equivalents in cell culture conditions before the transplantation onto a mouse, and (2) the limited availability and proliferative capacity of primary human cells, especially cells derived from patients with rare inherited skin diseases. A chamber grafting assay ( Wang et al, 2000 ; Diette et al, 2020 ) provides a simplified procedure for grafting primary human skin cells since the assay promotes the self-assembly of fibroblasts and keratinocytes in an in vivo environment without the need to produce skin equivalents in a dish. However, successful production of human skin equivalents in the grafting assay still requires at least 5 × 10 6 primary keratinocytes per 1.4 cm 2 of the wound area, which is a significant number when the availability of primary patient cells is limited.…”
Section: Introductionmentioning
confidence: 99%